2016
DOI: 10.1177/2333721415625293
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Tailored Health Promotion for Older Adults

Abstract: Objective: This study explores older adults’ perspectives on healthy living, and their interactions with professionals regarding healthy living. This perspective is necessary for health professionals when they engage in tailored health promotion in their daily work routines. Method: In a qualitative study, 18 semi-structured interviews were carried out with older adults (aged 55-98) living in the Netherlands. The framework analysis method was used to analyze the transcripts. Results: Three themes emerged from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…However, as also suggested by previous studies, our findings showed that older people may not always be receptive to proactive detection of risks and needs -that is, they are not always willing to anticipate future needs and can perceive attempt to encourage this as patronising [38,44]. Confidential relationships between older people and professionals, which are built on trust and tailored to people's needs, seem to be key to the success of such a proactive approach to care and support [38,[44][45][46]. Enabling professionals to cultivate such relationships, and ensuring they have adequate time to provide advice and communicate with older people about preferences and experiences, should therefore be an important aspect of integrated care services that aim to effectively address older people's safety.…”
Section: Discussionmentioning
confidence: 83%
“…However, as also suggested by previous studies, our findings showed that older people may not always be receptive to proactive detection of risks and needs -that is, they are not always willing to anticipate future needs and can perceive attempt to encourage this as patronising [38,44]. Confidential relationships between older people and professionals, which are built on trust and tailored to people's needs, seem to be key to the success of such a proactive approach to care and support [38,[44][45][46]. Enabling professionals to cultivate such relationships, and ensuring they have adequate time to provide advice and communicate with older people about preferences and experiences, should therefore be an important aspect of integrated care services that aim to effectively address older people's safety.…”
Section: Discussionmentioning
confidence: 83%
“…This is consistent with a study by Combs and colleagues (2013) who found that stroke patients’ wish to be walking farther was associated with the possibility of engaging in former activities and walking faster was associated with an improved walking ability. Also, Marcus-Varwijk and colleagues (2016) found that older adults prefer to live an active life and to be independent.…”
Section: Discussionmentioning
confidence: 99%
“…The need to feel and be independent was crucial and has also been described by Van Leeuwen et al (2019) and Halaweh et al (2018) showing that being independent allowed older people to feel free, enjoy a fulfilled life and hence, improve their quality of life. Healthy ageing is also described as associated to each person´s responsibility regarding their own independency (Marcus-Varwijk et al, 2016;Ten Bruggencate et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that strategies on healthy ageing and the development of age-friendly environments are necessary (Lloyd-Sherlock et al, 2012;Dattilo et al, 2015). The systems are often developed in specialized contexts (World Health Organization, 2015;Beard et al, 2016) and are thereby understood as such, as needs, expectations and opinions are described from the professional's' perspective rather than that of the old persons (Derksen et al, 2012;Marcus-Varwijk et al, 2016). Lette et al (2017) showed that old persons still living at home had different views about what was important in life compared to that of health care professionals.…”
Section: Introductionmentioning
confidence: 99%